Self-Dicslosure dan Parental Monitoring: Model Mediasi dengan Parental Knowledge - Sani, Indriawati Ghita Ghai; Riasnugrahani, Missiliana; Prasetya, Paulus H. (TAZKIYA Journal of Psychology, 2020)
Self-disclosure is an individual's actions to share information about himself to others, whether it is private, less intimate or even everyday information. Adolescent with the development of personal space sometimes need distance and keep many secrets from their parents, and tend to be more open to friends. Parents who are worried about the child's social and personal life will do parental monitoring. Parental monitoring efforts are partly influenced by the social signals displayed by children, meaning that the strength of parental monitoring can be influenced by the degree of self-disclosure. On the other hand, children who try to disclose sometimes get different responses such as reacting positively or negatively from parents. Therefore, we assume that the strength of parental monitoring will also be influenced by parental knowledge. Self-disclosure will be a source of parental knowledge, and this knowledge then determines parental monitoring. If parents do not use the child's disclose to increase knowledge about the child, then the child's self-disclosure will not affect parental monitoring. Through a proportional stratified random sampling technique, it was obtained 394 high school students, to see the link between self-disclosure and parental monitoring with the mediation of parental knowledge. Data were taken using parental monitoring scale from Kerr and Stattin (a=0.83), self-disclosure scale from Wheeless and Grotz (a=0.67), and parental knowledge from Kerr and Stattin (a=0.73). Mediation test results with the model 4 Hayes PROCESS obtained that the relationship between self-disclosure and parental monitoring is fully mediated by parental knowledge of 0.10. This means that self-disclosure in high school students will affect parental monitoring, only if parents have adequate knowledge about their children.